2010
DOI: 10.1111/j.1460-2695.2010.01472.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the effects of cold expansion of holes using thermoelasticity and image correlation

Abstract: A B S T R A C T Although cold expansion has been shown to have a positive effect on fatigue life, little work to date has been performed to evaluate the evolution of the strain field surrounding the crack tip on the mandrel entry and exit faces in cold-expanded coupons. Full-field strain measurements using both digital image correlation (DIC) and thermoelastic stress analysis (TSA) were used to compare the strains during crack growth around holes that had and had not been cold-expanded by 4%. Simple rectangula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 37 publications
3
24
0
Order By: Relevance
“…For this reason, the local amplitude, depending on both the remote stress and interference level, has been calculated and analysed. Therefore, some FEA have been carried out in order to confirm what is stated earlier . In Fig.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…For this reason, the local amplitude, depending on both the remote stress and interference level, has been calculated and analysed. Therefore, some FEA have been carried out in order to confirm what is stated earlier . In Fig.…”
Section: Resultsmentioning
confidence: 62%
“…The holes cause a geometrical discontinuity, which leads to stress concentration during the loading; furthermore, the drilling operation creates rough surfaces or localised damages, so that the fatigue life of component may be drastically reduced. Such situation forces a compensation of the fatigue life reduction that can be obtained with different techniques such as the cold expansion or the interference‐fit connections . The aim of the present paper was to characterise, from a microstructural and mechanical point of view, the 35 KB2 forging steel, investigating the effect of interference‐fit level on the fatigue life of holed plates, which are used in tracks chains of high power excavators (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Different destructive and nondestructive experimental methods, such as Sach boring‐out technique, X‐rays, and neutron diffraction technique, are applied to estimate the residual stress distribution because of cold expansion process. Nonetheless, it is demonstrated that these methods cannot determine the distribution of residual stress and plastic deformation precisely and mostly provide an averaged value of the stress or strain over a region . So to obtain the stress and strain distributions, finite element methods are widely used to analyse cold expansion process considering its nonlinear nature …”
Section: Introductionmentioning
confidence: 99%
“…Backman et al [7] have studied the effects of HCE by using Thermoelastic Stress Analysis (TSA) and Digital Image Correlation (DIC); by considering 2024-T3 aluminum alloy sheets they compared strains at the crack tip during crack growth around holes that had and had not been cold-expanded. Cracks originating from cold-expanded holes show lower strain values around the crack tip.…”
Section: Introductionmentioning
confidence: 99%
“…As it will be explained in the following sections, the proposed method allows the user to carry out an accurate analysis of the variation of the RS along the component thickness and consequently it permits the accurate experimental analysis of the RS actually introduced by the several HCE procedures proposed in the literature [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%